EVALUATION OF THE EXPERIENCE IN ENVIRONMENTAL TAX REFORMS IN THE EU COUNTRIES - Miceikiene, Astrida; Butvilaite, Ausra (European Scientific Journal, ESJ, 2015)
The urbanizing world, where human labour has been replaced by the mechanized machinery, is becoming increasingly dependent on the resources provided by nature. The demand of humanity in natural resources continues to grow. Due to the limitedness of the goods provided by nature, a human must take a more responsible approach towards the available resources by using the resources that are renewed more often and by protecting nonrenewable resources. Sustainable development is the field that analyses these paradigms. Social, economic, and environmental dimensions combined and the emphasis on one of the fiscal instruments for the purposes of sustainability bring forward the concept of environmental taxes. Environmental taxes may be interpreted as a fiscal instrument that transfers the tax burden from the “goods” onto the “bads”. Income generated by these taxes is distributed for stimulation of the sustainable economy based on conservation of the nature and more environmentally friendly production. The taxes considered may not only allow reducing the pollution and stimulating sustainable development of the national economy, but also influence the changes of the national tax structure. This article analyses the concepts of sustainable development, environmental taxes, and environmental tax reform. The development of environmental taxes, energy, transport, resources, and pollution in the selected EU countries is analysed. The analysis has shown that environmental taxes are sometimes allocated between the countries irrespective of whether a country has already implemented the environmental tax reform or not. In any case, each country should put own effort into environmental issues and seek sustainability.